Study on distinct quality properties of cashmere from local goat breeds of Mongolia (Mongolian Journal of Agricultural Sciences, 2022)
The research was carried out in 2021 to determine the specific quality properties of local Mongolian breeds of cashmere goats. The research covered 122 herder households from 13 soums in 8 aimags. A total of 4,560 samples were collected from 1,522 goats representing the main factors determining cashmere quality: ecological habitat, various herd management practices, local breeds, age and sex of goats, and cashmere colour. Cashmere fibre diameter (FD), fibre curvature (FC), and coefficient of variation of fibre diameter (CVFD) were tested in 1,522 samples, and cashmere length was tested in 1,387 samples. The overall mean fibre diameter (MFD) was 16.1 μm, mean length (FL) was 44.9 mm, and fibre curvature (FC) was 61.9°/mm. Cashmere from one-year-old goats was significantly finer than cashmere from older goats (about 1.0 μm, P